2009
DOI: 10.1016/j.otohns.2008.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Cochlear Implantation on Sacculus Function

Abstract: Although CI can cause damage to sacculus and hSCC function, this is probably not the only cause for postoperative vertigo. Advanced age is a significant risk factor for vertigo after CI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 20 publications
1
25
0
1
Order By: Relevance
“…After surgery, Todt et al (2008) found 13 of 28 patients with decreased cVEMP amplitudes. In the study by Krause et al (2009), four patients (50%) with preserved sacculus function preoperatively could also have cVEMP responses after the surgery. However, in all patients, there was a significant reduction of cVEMP amplitudes.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…After surgery, Todt et al (2008) found 13 of 28 patients with decreased cVEMP amplitudes. In the study by Krause et al (2009), four patients (50%) with preserved sacculus function preoperatively could also have cVEMP responses after the surgery. However, in all patients, there was a significant reduction of cVEMP amplitudes.…”
Section: Discussionmentioning
confidence: 96%
“…The data of oVEMPs after CI have not been reported yet. The rate of postoperative hypofunction was reported to be 13-86% in cVEMP (Todt et al, 2008;Krause et al, 2009;Licameli et al, 2009;Melvin et al, 2009;Krause et al, 2010;Wagner et al, 2010). Jin et al (2006)reported a response rate change in children with severe sensorineural hearing loss: seven of 12 patients presented normal cVEMPs before CI, but all disappeared after CI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the evaluation of saccular function after CI, only 500-Hz TB stimuli are used, and a wide range of cVEMP abnormalities have been reported [9][10][11][12] . It has been reported that cVEMP responses were not obtained, at a rate of 19%-62%, among patients with severe sensorineural hearing loss because of the anatomic and phylogenetic relationship of the cochlea with the vestibular organs, particularly the saccule; therefore, the extent of cVEMP responses and how CIs affect them remain unclear [13][14][15][16] .…”
Section: Discussionmentioning
confidence: 99%
“…Since it is recently known that low-frequency air-and bone-conducted stimuli can be used to test otolithic function also in humans [2], we wondered if such ''false-positive'' boneconduction thresholds in pure-tone audiometry could be linked to saccular function evaluated by cervical vestibular evoked myogenic potentials, cVEMP [1]. We therefore correlated the presence or the absence of obvious ''sensation thresholds'' in 29 patient (58 ears) with bilateral functional deafness (listed for cochlear implantation) with the respective presence or absence of cVEMPs when applying 500 Hz tone bursts (105 dB SPL, 7 ms duration, 5/s) via headphones and recording ipsilateral sternocleidomastoid muscle activity with surface electrodes [3].…”
Section: Dear Editormentioning
confidence: 99%